Anonymous
Anonymous asked in Science & MathematicsMathematics · 6 months ago

The logarithmic expression 3logbase2x - logbase2(2y) + 5 can be written?

a.) logbase2(3x^3/2y)

b.) logbase2(x^3/4y)

c.) logbase2 (16x^3/y)

d.) logbase2 (x^3/y^2) +5

4 Answers

Relevance
  • 6 months ago

    = 3.Log[2](x) - Log[2](2y) + 5 → recall: Log[a](x) = Ln(x) / Ln(a) ← where a is the base

    = [3.Ln(x) / Ln(2)] - [Ln(2y) / Ln(2)] + 5

    = { [3.Ln(x) - Ln(2y)] / Ln(2) } + 5 → recall: a.Ln(x) = Ln(x^a)

    = { [Ln(x³) - Ln(2y)] / Ln(2) } + 5 → recall: Ln(a) - Ln(b) = Ln(a/b)

    = { [Ln(x³/2y)] / Ln(2) } + 5 → recall: Log[a](x) = Ln(x) / Ln(a) ← where a is the base

    = Log[2](x³/2y) + 5

  • Vaman
    Lv 7
    6 months ago

    None seem to be the correct answer. If the question is 3 log base 2 x- 2 log base 2 y+5 then d is the correct answer.

  • 6 months ago

    Using log for log (base 2)....

    3 log(x) - logf(2y) + 5

    = log(x^3) - log(2y) + log(32)

    = log(32x^3/(2y))

    = log(16x^3/y)

  • Anonymous
    6 months ago

    Schools over U dumko

Still have questions? Get your answers by asking now.